Student outcomes from a long‐term outreach program working in rural and low‐income schools. Issue 12 (14th December 2020) - Warren, David
Abstract: The outreach program in the University of Otago Chemistry Department, focus in the FACS Chemical Education Award Lecture, has been running for more than 10 years. Over that time, it has worked in schools around New Zealand as well as delivering workshops at the Madam Curie High School Chemistry Camp in Taiwan and partnerships with a number of teacher training institutes in Malaysia. In addition to supporting schools and teachers in their chemistry teaching. The program also develops a wide range of skills and attitudes among the chemistry student volunteers who work delivering hands on activities. An overview of the program, the approach taken, and some examples of the activities will be followed by results of student interviews as they reflect on their development and learning. Abstract : Outreach or community engagement is frequently seen in terms of public education by scientists. However, it can be much more than that and a properly designed program can develop important skills in chemistry students. This article describes our approach to outreach, the benefits to students, and the development of a rubric that allows student progress to be monitored.